A new method for measuring the availability of the middle attacker in volleyball - Mercado Palomino, E.; Morante Rabago, J. C.; Parra Royón, M.; Benitez Sánchez, J. M.; Urena Espá, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In volleyball, some authors have considered the availability of the middle attacker as a measure of success (Costa et al., 2013). The use of measures that capture coordination in sports, such as geometrical centres as network analysis, have been increasing in different levels of team sports (Davids, 2013). These variables are expected to describe accurately complex systems states of coordination and temporal dynamics (Duarte et al., 2012). Notwithstanding, the spatial precision supposes a common limitation on observational studies. The present study intended (a) to develop a support tool to improve the registration of the position in the court; (b) to discover the area of action of the setter when there is availability of the middle attacker; and (c) to find a summary value that allows the comparison between teams and their relationship with other variables. Methods: Volleyball Men`s World Championship 2010 in Italy was analyzed, with a total of 23 games and represented by 12 national teams, using the variables Latitude and Depth of the setter, and calculating the centroid, the vector and the angle for each team. These variables were calculated by the developed support tool, which allows us to register exactly the position of the setter using an adaptable grid on the court. The data were recorded with the software of observational analysis applied to volleyball VA-Sports. Results: From the positions of the setter were created specific profiles of each team where the centroid was calculated from the weighted average of the density of the frequencies. This makes possible to calculate the availability of the middle attacker through the vector, which is the distance between the centroid and the ideal zone of setting. The centroids of the teams vary between 1.049 and 1.468 meters. Discussion: In conclusion, the centroid is a summary value of the area of availability of the middle-attacker, allowing us to make comparisons between teams, from the setting frequencies distribution, as well as it could be a future performance indicator.